"Battlefields" of blue flags and seahorses: Acts of "fencing" and "de-fencing" place in a gold mining controversy. (November 2017) - Hovardas, Tasos
Abstract: The objective of the present study was to investigate how meanings of place were constructed to shape contrasting positions in a gold mining conflict in Greece, and the implications of these dynamics for place-attachment. A social divide has gradually deepened in the area, separating employees of the mining company, on the one side, from residents involved in agriculture, forestry, fishing, and tourism, on the other. Local people engaged in the conflict were interviewed and interview data were analysed in the frame of discursive positioning of respondents, in order to follow how place-based referents were voiced. Acts of positioning might be approached as acts of "fencing", namely acts of designating specific areas and assigning specific significations or place-based projects to them. These acts were followed by counter-acts of "de-fencing", namely, acts of challenging significations attempted by the opposing side. Implications of the study for future research are discussed. Highlights: Rival interpretations were approached within the frame of discursive positioning. "Fencing" or "de-fencing" place could involve offensive or defensive acts. Acts of positioning implied a re-arrangement of civil society in the study area.